Secular Macroeconomic Theorems - Kurihara, Kenneth K. (The Review of Economics and Statistics, 1952)
M ACROECONOMIC behavior in the long run is characterized by two seemingly contradictory features, namely, by certain persistent tendencies and by incessant change. But these features are part and parcel of the same pattern of historical development in the economic field as well as in other fields. This note is an attempt to conceptualize Keynes's and others' vision of what is relevant for understanding the secular behavior of advanced capitalism, of economies. Such an attempt will be made here by means of a series of propositions in order to provide an analytical frame of reference. Secular macroeconomic behavior is influenced by (a) certain endogenous characteristics of the economic machine, and (b) exogenous factors of a fundamental nature. It is possible to make rigorous long-run statements by indicating what stands out as the general trend under varying historical circumstances. Broadly speaking, we may say that the general trend of mature economies is what it is because exogenous factors react on the inherent or endogenous variables of the economic process itself. First, I wish to bring out the long-run aspect of Keynes's multiplier theory ' in order to see its bearing upon continuous stability in varying degrees of economic development. Here we consider the multiplier as a structural coefficient and the consumption function as historically given. Our fundamental theorems based on Keynes's long-run observations 2 are: employment corresponding to given fluctuations in investment. 2. The lower the average propensity to consume, the greater the preponderance of capitalgoods industries in the economy and the greater also the degree of instability associated with those industries.